2021
DOI: 10.1111/mam.12235
|View full text |Cite
|
Sign up to set email alerts
|

Diet composition of the golden jackal Canis aureus in south‐east Europe – a review

Abstract: The golden jackal Canis aureus is spreading throughout Europe and settling in countries where it has never been found before. Understanding its trophic ecology is increasingly important as it colonises new areas and ecosystems. This paper aims to review the diet studies that have been performed on the golden jackal in Europe and provide a complete overview of its food intake, feeding behaviour and strategy. Golden jackals were found to eat mainly small mammals (54% biomass), followed by domestic animals, ungul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
11

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 31 publications
1
9
0
11
Order By: Relevance
“…Vegetation consumption was greater during the summer and autumn when many fruits are most available. This pattern is similar in other omnivorous canid species – reviews of Iberian red fox and golden jackal diets also found greater consumption of vegetation in the summer and autumn (Díaz‐Ruiz et al 2013, Lange et al 2021). Indeed, the sharp increase in vegetation consumption during the summer and autumn we found could partially explain the negative relationship between it and both ungulate and lagomorph consumption.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Vegetation consumption was greater during the summer and autumn when many fruits are most available. This pattern is similar in other omnivorous canid species – reviews of Iberian red fox and golden jackal diets also found greater consumption of vegetation in the summer and autumn (Díaz‐Ruiz et al 2013, Lange et al 2021). Indeed, the sharp increase in vegetation consumption during the summer and autumn we found could partially explain the negative relationship between it and both ungulate and lagomorph consumption.…”
Section: Discussionsupporting
confidence: 68%
“…Each of the 12 food categories except wild pigs received a value for each season in a study (i.e. we entered a zero if the category was not reported; Lange et al 2021). We chose this approach because we assumed that, unless we had reason to believe otherwise (and had excluded the study; see criteria seven and eight above), authors reported coyote diets comprehensively.…”
Section: Methodsmentioning
confidence: 99%
“…The golden jackal is a medium‐sized opportunistic mesopredator with a broad range of food categories, including small mammals (mainly rodents), birds (and their eggs), amphibians, reptiles, invertebrates, and sporadically plants (especially fruits) (Farkas et al, 2017 ; Gherman & Mihalca, 2017 ; Lange et al, 2021 ; Lanszki et al, 2016 ; Penezić & Ćirović, 2015 ; Torretta et al, 2021 ). This flexible and generalist diet of the golden jackal is supposed to promote the currently observed area expansion (Hatlauf et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interacting with numerous other species (parasites, prey, and competitors) the golden jackal is part of complex food webs, predator–prey relationships, and host–parasite relationships (Gherman & Mihalca, 2017 ; Lange et al, 2021 ; Lanszki et al, 2016 ). The species plays a prominent role in the ecosystem as a canid mesopredator.…”
Section: Introductionmentioning
confidence: 99%
“…The studies of geographical variation in diet composition of golden jackal indicated the influence of some abiotic and biotic factors (e.g. latitude, longitude, environmental productivity, land use, anthropogenic resources) on diet composition (Ćirović et al, 2016; Lange et al, 2021; Lanszki et al, 2016; Lanszki, Hayward, Ranc, & Zalewski, 2018; Tsunoda & Saito, 2020). However, these studies did not compare diet variation between historic and recently colonized ranges in relation to variation in biotic and abiotic conditions.…”
Section: Introductionmentioning
confidence: 99%